STRATEGI KOMUNIKASI DIGITAL POLRI DALAM MEMBANGUN REPUTASI POLDA LAMPUNG DI MEDIA SOSIAL - Agus, Isnandar; Rohani; Wijaya, Muhammad Andri; Suhardi, Tri (Jurnal Bisnis Darmajaya, 2025)
The dynamics of public reputation and trust in the Indonesian National Police are influenced by news coverage and social media discourse. Yet, comprehensive studies on the strategic communication practices of the Public Relations Bureau of the Lampung Regional Police in strengthening institutional reputation in digital spaces remain limited. This study aims to analyze the digital communication strategies of Bidang Humas Polda Lampung and to evaluate its social media management in efforts to build, maintain, and strengthen institutional reputation. Using a qualitative case study design, the research covers the 2022–2024 period. Data were collected through semi-structured interviews, observation, and content documentation from official channels (Instagram, TikTok, Facebook, X, and the official website), with source and method triangulation. The findings indicate targeted digital communication management through systematic content planning, cross-platform message adaptation, coordinated issue response and clarification, and responsive, ethical two-way interaction. The study also maps three key aspects: the workflow of public communication management, cross-platform channel utilization, and public interaction patterns associated with reputation. The study recommends strengthening personnel capacity, refining operational guidelines for issue management, and conducting periodic evaluations using platform analytics to ensure that digital communication strategies are implemented consistently and sustainably.